Flexed position of the wrist in the cast reliably prevents displacement after physeal Salter-Harris I and II distal radius fractures - Kralj, Rok; Kurtanjek, Mario; Gržan, Ivan Silvije; Bumči, Igor; Višnjić, Stjepan; Žic, Rado (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2024)
Background Salter-Harris I and II fractures of the distal radius are common injuries. In our facility, immobilisation is performed in a way that counteracts angulation forces. The aim of our study was to determine whether there are significant differences between patients with and patients without a loss of reduction treated with this method and to determine what degree of flexion reliably prevents secondary displacement.Patients and methods We conducted a retrospective study of 112 patients (mean age: 12 years) who had sustained a Salter-Harris type I or II fracture of the distal radius and were treated with reduction. Patients were grouped according to fracture type and whether they sustained a loss of reduction or not. Patients were compared for gender, age, initial angulation, angulation after reduction, degree of flexion/extension of the wrist in the cast, residual angulation, duration of immobilisation, and complication rate. We also analysed whether a 45-degree flexed position of the wrist in plaster provides reliable protection against secondary displacement.Results In group I, patients with no loss of reduction had a significantly greater degree of wrist flexion in the cast, a significantly shorter duration of immobilisation and significantly less residual angulation. Patients with an apex-volar deformity with the wrist immobilised at more than 45 degrees of flexion had no loss of reduction at all and had significantly less residual angulation compared with patients with the wrist immobilised at less than 45 degrees of flexion. In this patient group, loss of reduction was noted in 28% of cases. The patients in group II with loss of reduction showed a significantly higher angulation after the reduction. During the follow-up examination, one patient experienced physeal arrest followed by an ulnar impaction syndrome. Other complications recorded were minor.Conclusions In summary, based on our results, we recommend that all physeal fractures of the distal radius with an apex-volar angulation can be safely treated with reduction and immobilisation counteracting the forces of angulation. For apex-dorsal fractures, palmar flexion of 45° allows for reliable reduction.
Keywords: physeal; distal; radius; fracture; paediatric